Workplace Policy and Associated Factors of Minimum Acceptable Diet Practices: An Online Survey Among Working Mothers in Indonesia - Deandra, Fadhila Iswi; Februhartanty, Judhiastuty; Mansyur, Muchtaruddin (Kesmas, 2025)
Working mothers in Indonesia may influence complementary feeding practices, particularly their ability to ensure that their infants properly meet the minimum acceptable diet (MAD). In this cross-sectional study, an online survey was distributed through various online platforms where participants were recruited using convenience sampling. The questionnaire covered sociodemographic factors, workplace policies, and infant and young child feeding (IYCF) practices. Descriptive and logistic regression analyses were conducted. A total of 394 working mothers participated, of which over 90% of the respondents reported meeting minimum dietary diversity, minimum milk frequency, minimum milk feeding frequency, and MAD indicators as assessed with a standardized questionnaire based on the WHO’s IYCF assessment. Multivariate analysis identified two workplace policy variables significantly associated with meeting MAD requirements: physical facility support (AOR: 2.99; 95% CI [1.03, 8.70]; p-value <0.05) and workplace flexibility scores (AOR: 0.18; 95% CI [0.05, 0.65]; p-value <0.05). These findings highlighted the importance of having supportive workplace environments that enable working mothers to ensure that their infants meet MAD requirements. Additionally, the negative association between workplace flexibility and meeting MAD requirements may have been due to the homogeneity of this study’s subjects' characteristics.